PRINCIPLES OF POLICE ACTION IN POLICE LAW - Matvejevs, Aleksandrs (Administrative and Criminal Justice, 2019)
The author of the article study problems of enforcement and implementation of principles in activities of police and mechanisms of implementation of principles in activities conducted by police. Its mean that the operations of the police shall be organised observing lawfulness, humanism, human rights, social justice, transparency and an undivided authority, and relying on the assistance of the public. The police shall protect the rights and lawful interests of persons irrespective of their citizenship, social, economic and other status, race and nationality, gender and age, education and language, attitude towards religion, political and other convictions. The police, by its operations, shall ensure the conformity with the rights and freedoms of persons. Restriction of such rights and freedoms shall be permitted only on the basis of law and in accordance with procedures specified in law. Author discloses the meaning and content of the principles of the organization and activities of the police, enshrined in the law. The authors also stress out particular disadvantages of law ”On Police” and make suggestions how to improve it.